Historia sztuki i medycyna - Kędziora, Łukasz (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
<div style="font-size: 16.25px; font-family: serif; left: 158.72px; top: 929.658px; transform: rotate(0deg) scale(0.927016, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-canvas-width="385.54587499999997" data-font-name="g_font_82_0" data-angle="0">The article Art history and medicine concerns selected aspects of the Medicine in art exhibition, taking place at the Museum of Contemporary Art in Kraków (MOCAK) between 22nd April and 22nd October 2016. The author discusses the issue of medicine with regard to its mechanisms that let us create and perceive art. This reflection includes a historical overview of the “medically-oriented” art research. Another significant aspect constitutes the attempt to explain by the tools associated with neuroaesthetics, why the viewers are likely to look at some drastic images created by artists with such willingness and involvement. The analysis refers to texts by D. Freedberg, V. Gallese, A. Damasio, P. Przybysz, and others. It also includes interpretations of the photohraph Seated anatomical model by Zoe Leonard, as well as the Medical Kit installation by Wilhelm Sasnal.